A dimensão da janela na obra de Eduardo Souto de Moura - Cristiano Manuel Sousa Vaz Silva (2023)
The window has been an integral part of Man's building for thousands of years, since its invention. As an architectural element, it exists both inside and outside of buildings. Its symbolism, historical context, and its technological, material, cultural, and social evolution are the core of my reflection in this study. This dissertation focus on the scale of the 'dimension' of the window in architecture: the historical and temporal dimension, the symbolic dimension, the technical dimension and the metric dimension. I have been in contact with the aluminium metal work industry for about eight years, collaborating on execution projects and contributing in various works, to the design of minimalist frame solutions, and more recently, facades systems. This professional experience has provided me with technical knowledge of aluminium metal work focused on architecture, which sparked my interest in the topic. I highlight the contribution of architect Eduardo Souto de Moura to the evolution and understanding of the 'window,' drawing from the manifestos of his masters from the past and our contemporaries, in connection with the constant innovations in the industry. The House in Quinta do Lago, the study subject in this dissertation, was target of two interventions by this architect at different times. In the most recent intervention, in 2018, I was part of the technical team responsible for specifying aluminium frame solutions through the company I collaborated with, which reinforced the choice of this work. In this study, I do an exercise of reinterpretation of the building elevations, reflecting various expressions of the openings. I analyze the proportion, the metrics of the 'window,' and its relation with others parts, as well as the technical concepts of construction and tectonics that elucidate the understanding of his work.